PREFERENSI MASYARAKAT TERHADAP TRANSPORTASI PUBLIKDI KOTA BANDA ACEH(Studi Kasus Bus Trans Koetaradja) - Henri Prianto Sinurat; Jul Fahmi Salim; Citra Permatasari (Universitas Teuku Umar, 2020)
This study aims to look at the factors that influence the preferences of the people of Banda Aceh in using the Trans Koetaradja Bus. The data used are primary data obtained from distributing questionnaires electronically through Google forms, the number of respondents who filled Google Forms was 57 respondents. The results of the study show that the preferences of the people of Banda Aceh City are significantly influenced by the level of income, the higher th e level of opinion of a person, the smaller the level of use of Trans Koetaradja Buses, while the travel time to bus stops and distance does not significantly influence the intensity level of the use of Trans Koetaradja Bus in the city of Banda Aceh Keywords: Trans Koetardja, Income, Transportation